GAYA BAHASA SINDIRAN DALAM TAYANGAN MAIN HAKIM SENDIRI DAN BERCANDA TAPI SANTAI (BTS) - Maghfirah Warahmah; Fitrawahyudi Fitrawahyudi; Irwan Fadli (Universitas Negeri Makassar, 2026)
This study aims to analyze the use of satirical language styles by each actor in the shows Main Hakim Sendiri and Bercanda Tapi Santai (BTS) using stylistic analysis. This study used a qualitative research type with a descriptive approach. The research data were taken from sentences, expressions, and words from the actors that have been transcribed in the shows Main Hakim Sendiri and Bercanda Tapi Santai (BTS). The data collection techniques used were observation and documentation. The data analysis technique used the Miles and Hubberman model, which includes data reduction, data presentation, and conclusion drawing. The results showed that there were seven data points on satirical language styles in the shows Main Hakim Sendiri and Bercanda Tapi Santai (BTS), which included four figures of speech, namely irony, cynicism, satire, and sarcasm, and no innuendo figures of speech were found. Significant differences were seen in the show Main Hakim Sendiri, where irony figures of speech were found without the use of harsh words, while Bercanda Tapi Santai did not find irony figures of speech but often used harsh curses in the form of sarcasm.